PENGARUH ENVIRONMENTAL COST DAN ENVIRONMENTAL PERFORMANCE TERHADAP FINANCIAL PERFORMANCE (Studi Kasus pada Perusahaan Sektor Pertambangan Peserta PROPER Periode 2012 – 2016) - Nababan, Lastri Meito; Hasyir, Dede Abdul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.03.TAHUN 2019, 2019)
As a result of their activities, companies are demanded by stakeholders to perform in accordance with the concept of triple bottom line: financial aspects (profit), environment (planet), and social (people). This study aims to examine the effect of environmental costs and environmental performance on the company's financial performance. Environmental costs data are retrieved from the company's sustainability reports, environmental performance is then measured by PROPER ratings, and financial performance is proxied by return on assets (ROA). In addition, company size is employed as control variable. Through purposive sampling method, seven companies were selected in the mining industry sector in the period 2012-2016 as samples. This study uses multiple linear regression analysis to test the hypothesis. The results of the research both simultaneously and partially show that environmental costs and environmental performance have a significant influence on financial performance. It can be concluded that the greater the environmental cost and the better the environmental performance (PROPER) can increase the financial performance (return on assets) of the company. Firm size as a control variable is significantly associated with environmental costs and environmental performance. The hypothesis formulated in this study was accepted and has been supported by statistical research results.